(untitled) (Research, Society and Development, 2023)
Food and nutrition education stands out as an area of activity of nutrition professionals in the school scenario, which has as its main strand the promotion of the health of students considering their knowledge about food and nutrition. This study aimed to identify the importance of nutritional education for preschool development. Through a bibliographic and documentary research on the platforms Pubmed, Scielo and Lilacs, with a survey of studies already conducted on the subject, 12 articles were selected that met the eligibility criteria and the objectives of the research. While results, it was identified that the most effective methodologies of action with students for the promotion of a food and nutritional education occur mainly when approaching the reality of the student, such as playful strategies, practical activities, among others. In this scenario, the elaboration of concrete material, the construction of community gardens, the holding of conversation circles and dialogued lectures were pointed out as effective methodologies for achieving an efficient food and nutrition education.